2017
DOI: 10.1186/s13568-017-0504-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of chromium and tannic acid bioremediation by Aspergillus niveus using Plackett–Burman design and response surface methodology

Abstract: A chromium and tannic acid resistance fungal strain was isolated from tannery effluent, and identified as Aspergillus niveus MCC 1318 based on its rDNA gene sequence. The MIC (minimum inhibitory concentration) of the isolate against chromium and tannic acid was found to be 200 ppm and 5% respectively. Optimization of physiochemical parameters for biosorption of chromium and tannic acid degradation was carried out by Plackett–Burman design followed by response surface methodology (RSM). The maximum chromium rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…However, in traditional ‘one-factor-at-a-time’ experiments, the effects of various factors can only be investigated one at a time, and this approach fails to evaluate multifactorial interactions among all components, thereby leading to inefficient and time-consuming work (Lee 2018). Response surface methodology (RSM) includes factorial designs and regression analysis for construction of empirical models, making it an excellent statistical tool for increasing the production of valuable metabolites (Chaudhary et al 2017; Fu et al 2016). RSM can evaluate all the factors simultaneously and determine the optimal culture conditions for microbes.…”
Section: Introductionmentioning
confidence: 99%
“…However, in traditional ‘one-factor-at-a-time’ experiments, the effects of various factors can only be investigated one at a time, and this approach fails to evaluate multifactorial interactions among all components, thereby leading to inefficient and time-consuming work (Lee 2018). Response surface methodology (RSM) includes factorial designs and regression analysis for construction of empirical models, making it an excellent statistical tool for increasing the production of valuable metabolites (Chaudhary et al 2017; Fu et al 2016). RSM can evaluate all the factors simultaneously and determine the optimal culture conditions for microbes.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the adjusted determination coefficient (Adj R-squared, Table 9) (0.82 > 0.80) and coefficient of variance (CV%) was 9.19, which further indicated that the multivariate regression relationship between the dependent variable and the all independent variables was significant [31]. In other words, the regression equation was adequate in predicting the optical density (OD600) under different fermentation conditions [32] ( Figure 6). The profiles of the response surfaces between fermentation time and inoculum level, fermentation time and pH, inoculum level and pH were all convex with an open downward direction, indicating a parabolic relationship between the OD600 value and the three factors of fermentation time, inoculum level and pH [33].The surface plots showed the interactive effects of the three significant fermentation factors on the bacterial growth.…”
Section: Optimization: Box-behnken Designmentioning
confidence: 79%
“…At the same time, the adjusted determination coefficient (Adj R-squared, Table 9) (0.82 > 0.80) and coefficient of variance (CV%) was 9.19, which further indicated that the multivariate regression relationship between the dependent variable and the all independent variables was significant [31]. In other words, the regression equation was adequate in predicting the optical density (OD 600 ) under different fermentation conditions [32] (Figure 6). level) > X1 (Time).…”
Section: Optimization: Box-behnken Designmentioning
confidence: 80%
“…By moving each variable from the chosen reference point while keeping the other variables at constant reference values, the response changes are presented in the perturbation plot. 50 As shown in Figure S2 , the curve with the most notable change was the fermentation period (A) followed by culture temperature (B). The least notable variable was defined as antifoam reagent addition (C).…”
Section: Resultsmentioning
confidence: 99%